Public–private collaboration in the provision of palliative care for children and adolescents with cancer: A Chilean experience. Issue 6 (29th May 2021) - Fernández, Jazmine; Roje, Dunja; Rossell, Nuria; Zubieta, Marcela
Abstract: Background: In Chile, children and adolescents with cancer in need of palliative care receive services through a collaborative scheme run in coordination between the hospitals of the public health system that attend children with cancer and the non‐profit civil society organization Fundación Nuestros Hijos (FNH). Aim: The main objective of this article is to offer a summary of the Chilean experience in the provision of palliative care services for children and adolescents with cancer, as an example of a public‐private partnership that improves the quality of life and the end‐of‐life experience for the children, adolescents, and their families. Methods and results: The palliative care program works with the children and their families as main members of the team, providing medical services for pain and symptom alleviation, psycho‐social support, rehabilitation for the improvement of quality of life, and aid to secure the best physical conditions for the child at home or in temporary housing for the whole family. Conclusion: The private‐public collaboration between the Chilean health system and the FNH is a successful model to help families suffering the devastating loss of a child.